Smoking and pulmonary sarcoidosis: effect of cigarette smoking on prevalence, clinical manifestations, alveolitis, and evolution of the disease. Issue 7 (July 1988) - Valeyre, D; Soler, P; Clerici, C; Pré, J; Battesti, J P; Georges, R; Hance, A J
Abstract : Patients with pulmonary sarcoidosis are less likely to smoke than persons of a similar age in the general population. This could be because smoking reduces the likelihood of developing sarcoidosis, or alternatively smoking could reduce the severity of the disease process so that smoking patients are underrepresented among patients with clinically overt disease. To evaluate these possibilities 64 patients with sarcoidosis of recent onset were studied at presentation and after a one year follow up period, clinical, functional, radiographic, and bronchoalveolar lavage fluid criteria being used to identify factors that might account for the lower incidence of sarcoidosis in smokers and to determine whether the disease is less severe in smoking patients. Smoking was less common in the patients with sarcoidosis (30%) than in the control subjects (46%). The study did not support the conclusion that sarcoidosis is less severe in smokers, as clinical, radiographic, and functional abnormalities were similar in smokers and non-smokers at initial evaluation and after a one year follow up period. Nevertheless, smoking did influence various indices used to assess disease "activity." Cigarette smoking was associated with a significant increase in the serum angiotensin converting enzyme activity (SACE), and patients with very high SACE and pulmonary gallium-67 uptake were smokers. Furthermore, more CD8+ (but not CD4+) lymphocytes were recovered by lavage from smoking than from non-smoking patients, giving a lower CD4: CD8 ratio in smokers. Fewer alveolar macrophages were recovered by lavage from smokers with sarcoidosis than from normal subjects with a similar smoking history. These finding support the possibility that smokers, particularly those with a prominent accumulation of alveolar macrophages in the lower respiratory tract, may be less likely to develop sarcoidosis.